The feeling of guilt, the super-ego and the pulsion of death (1992)
The article wants to show the modifications that appear in the psychoanalytic theory starting from the presence of the concept of the pulsion of death. Before the pulsion of death existed severe difficulties to explain certain characteristic phenomenons of the super-ego or of the limitations that one met in the therapeutic processes. The instinct death appears as an impossible subject for the psychoanalysis and despite of this its conceptualisation is fundamental.